Exploring the conceptualization, operationalization, implementation, and measurement of outreach in community settings with hard-to-reach and hidden populations: A scoping review. (September 2022) - Jiao, Sunny; Slemon, Allie; Guta, Adrian; Bungay, Vicky
Abstract: Outreach is as a strategy employed by those in health and social services, which generally involves establishing relationships and providing support to people situated in hard-to-reach and hidden populations. However, there is a lack of clarity across the literature on how outreach is conceptualized, the central elements of outreach as a program and practice, and how the 'success' of outreach is empirically measured. Such gaps limit understandings of how outreach can be most effectively implemented and evaluated. The purpose of this scoping review responds to these challenges by systematically examining how outreach has been conceptualized, operationalized, and evaluated in community settings with hard-to-reach and hidden populations. This scoping review approach was undertaken in accordance with the 6-step framework developed by Arksey and O'Malley and advanced by Levac and colleagues. The search was conducted across four databases (CINAHL, MEDLINE, PubMed, and PsycINFO) and included research, review, and non-empirical articles published in English between January 1, 2008 and April 20, 2020.16, 238 records were screened by title and abstract, followed by a review of 654 full-text articles and critical appraisal of 67 articles. Forty-two articles were included in the review, including 28 research articles (90%), two review, and two non-empirical. Findings illustrate that there is considerable variation in how outreach is conceptualized, implemented, and evaluated across the literature. Further, outreach is often inadequately defined, and predominantly overlooks the underlying and systemic reasons for clients' "disengagement" from health and social care. Outreach providers and researchers are encouraged to draw on client-led aims, goals, and outcome measures to determine the enactment, evaluation, and measurement of outreach, and to explicitly position outreach as working alongside clients to remove structural barriers to care. Highlights: Outreach involves the navigation and mitigation of structural barriers to care. There is a need to acknowledge systemic reasons for disengagement and disconnection. Measurements of outreach should account for context and reflect client goals.